2017
DOI: 10.18535/ijsrm/v5i11.21
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Age and Sex on Bystander Cardiopulmonary Resuscitation Knowledge

Abstract: Objective: To assess the impact of age and sex on the bystander CPR Knowledge in a group of Nigerian student teachers. Materials and Methods: A quasi-experimental study design was used with the cohort made up of forty one (41) male and forty one (41) female undergraduate students of Physical and Health Education with 40 participants in the 17-20 years age group and 42 participants belonging to the 21-28 years of age bracket were randomly selected from the larger main cohort for analysis of possible impact of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…According to Dobbie et al [7], "the older a person was, the less likely they were to be CPR trained, show willingness to be CPR trained or be confident to administer bystander CPR with or without instruction from an emergency call handler". None of the earlier Nigerian studies on bystander cardiopulmonary resuscitation in relation to age and gender [8][9][10][11][12] did involve athletes. Some studies globally on bystander cardiopulmonary resuscitation have shown clearly the associated increased risk of sudden cardiac arrests among athletes [13][14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…According to Dobbie et al [7], "the older a person was, the less likely they were to be CPR trained, show willingness to be CPR trained or be confident to administer bystander CPR with or without instruction from an emergency call handler". None of the earlier Nigerian studies on bystander cardiopulmonary resuscitation in relation to age and gender [8][9][10][11][12] did involve athletes. Some studies globally on bystander cardiopulmonary resuscitation have shown clearly the associated increased risk of sudden cardiac arrests among athletes [13][14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%